Působení ženských řeholních řádů v českém pohraničí: Průniky církevních a laických světů - Vodáková, Olga (Lidé města, 2020)
This article maps out the relation between women’s religious orders forced to work in the Czech borderlands (namely the Šluknov Hook) in the period of 1950–1993 with the lay, secular community. It deals with each of the orders and their specifics and describes their work with clients of nursing homes and of social welfare institutions. It attempts to answer the question of what such forced labour brought about for both parties, and what has changed since the nuns have left the studied locations. The study also points out the fact that as yet, the given, quite specific subject matter has almost never been treated. The study is also based on internal, yet-to-be published materials